Samarinda City Branding through Tourism Communication of Dayak Village in Pampang - Tuti Widiastuti; Eli Jamilah Mihardja; Prima Mulyasari Agustini (MediaTor (Jurnal Komunikasi), 2020)
The Dayak village in Pampang, Samarinda in East Kalimantan has cultural potential, especially the performing arts that is utilized to support the development of regional tourism. For this reason, this study aims to find out how Dayak cultural symbols in the village of Pampang is used for the strategy of Samarinda city branding. The symbolic of interaction perspective is used to analyze the use of cultural symbols in the imaging of a city. The research method used is descriptive qualitative. Data are collected from interviews with various informants from the government, community leaders, and traditional leaders. Finding of the research indicated that the performing arts is used as a resource in tourism development with a cultural perspective. Cultural symbols in the performing arts can be a means of symbolic interaction of the Dayak culture in Pampang among the community, domestic and foreign tourists who come to this village. This cultural performing can be an attraction of Samarinda City, which has minimal potential for a nature tourism. The utilization of regional cultural potential can be maximized by increasing support from formal and informal institutions to manage this potential to support the image of the city.